Comparative satisfaction of receiving medical abortion service from nurses and auxiliary nurse-midwives or doctors in Nepal: results of a randomized trial - Anand Tamang; Iqbal H. Shah; Pragya Shrestha; I. K. Warriner; Duolao Wang; Kusum Thapa; N. T. My Huong; Olav Meirik (BMC, 2017)
Abstract Background Early first-trimester medical abortion (MA) service (≤ 63 days) has been provided by doctors and nurses under doctors' supervision since 2009 in Nepal. This paper assesses whether MA services provided by specifically trained and certified nurses and auxiliary nurse-midwives independently from doctors' supervision, is considered as satisfactory by women as those provided by doctors. Methods The data come from a multi-center, randomized, controlled equivalence trial conducted between April 2009 and March 2010 in five district hospitals in Nepal. Women seeking MA were randomly assigned to doctors or nurses and auxiliary nurse-midwives(ANMs).Eligible women were administered 200 mg mifepristone orally followed by 800 μg misoprostol vaginally two days later by their assigned providers and followed up 10-14 days later. At the follow-up visit women's reported satisfaction with MA service they received was measured. Results Of 1295 women screened for eligibility, 535 were randomly assigned to a doctor and 542 to a nurse or ANM. Nineteen women were lost-to-follow up in the former group and 27 were lost-to-follow up or did not complete the acceptability interview in the latter group. This study is, therefore, based on516womenin the doctor's group and 515 women in the nurse or ANM group. All women in the nurse or ANM group reported being satisfied or highly satisfied by MA compared to 99% in the doctor's group. Satisfaction was similar regardless of the type of provider; 38% among nurse or ANM and 35% among the doctor group were "highly satisfied", and 62% and 64%, respectively, were "satisfied". Women's experiences such as 'less than expected amount or duration of bleeding following MA', 'shorter than expected duration of the abortion process', and 'able to manage symptoms', were found to be associated with women's higher satisfaction with MA. Counseling and information on the method, potential complications of MA and post-abortion contraception was nearly universal. No statistically significant differences were found in the level of satisfaction by age, parity, marital status, education or occupation of women. Conclusions Women's satisfaction with MA service provided by trained nurses or auxiliary nurse-midwives was similar to that provided by doctors. The findings, therefore, provide support for extending safe and accessible medical abortion services by government-trained nurses and auxiliary nurse midwives to women seeking early first trimester pregnancy termination. Trial registration The trial was retrospectively registered with ClinicalTrials.gov (identifier: NCT01186302 ). Registered August 20, 2010.